Markers of inflammation and multiple complex stenoses (pancoronary plaque vulnerability) in patients with non-ST segment elevation acute coronary syndromes. Issue 8 (14th July 2004) - Avanzas, P; Arroyo-Espliguero, R; Cosín-Sales, J; Aldama, G; Pizzi, C; Quiles, J; Kaski, J C
Abstract : Objective: To assess the relation between markers of inflammation and the presence of multiple vulnerable plaques in patients with non-ST segment elevation acute coronary syndromes. Design: Prospective cohort study of 55 patients with non-ST segment elevation acute coronary syndromes and angiographically documented coronary disease. Blood samples were obtained at study entry for the assessment of high sensitivity C reactive protein (CRP), neopterin, and neutrophil count. Coronary stenoses were assessed by quantitative computerised angiography and classified as "complex" (irregular borders, ulceration, or filling defects) or "smooth" (absence of complex features). Extent of disease was also assessed by a validated angiographic score. Results: Neutrophil count ( r = 0.36, p = 0.007), CRP concentration ( r = 0.33, p = 0.02), and neopterin concentration ( r = 0.45, p < 0.001) correlated with the number of complex stenoses. Patients with multiple (three or more) complex stenoses, but not patients with multiple smooth lesions, had a higher neutrophil count (5.9 (1.4) × 10 9 /l v 4.8 (1.4) × 10 9 /l, p = 0.02), CRP concentration (log transformed) (1.08 (0.63) v 0.6 (0.6), p = 0.03), and neopterin concentration (log transformed) (0.94 (0.18) v 0.79 (0.15), p = 0.002). Multiple regression analysis showed that neopterin concentration (B = 4.8, 95% confidence interval (CI) 1.9 to 7.7, p = 0.002) and extent of coronary artery disease (B = 0.6, 95% CI 0.03 to 1.2, p = 0.04) were independently associated with the number of complex stenoses. Conclusions: Acute inflammatory markers such as high neutrophil count, CRP concentration, and neopterin concentration correlate with the presence of multiple angiographically complex coronary stenoses. Neopterin concentration was a stronger predictor of multiple complex plaques than were neutrophil count and CRP concentration. These findings suggest that a relation exists between inflammation and pancoronary plaque vulnerability.